Hexenlust und Sündenfall die seltsamen Phantasien des Hans Baldung Grien ; [... anläßlich der Ausstellung "Hexenlust und Sündenfall. Die seltsamen Phantasien des Hans Baldung Grien", Städel Museum, Frankfurt am Main, 24. Februar - 13. Mai 2007] = Witches' lust and the fall of man : the strange fantasies of Hans Baldung Grien / exhibition and catalogue by Bodo Brinkmann ; with an essay by Berthold Hinz - Hinz, Berthold 1941- (Imhof, 2007)
"Hans Baldung Grien (1484-1545) created many drawings and etchings depicting the fantastic behaviour of witches, but only one painting, the world famous "Two Witches" (1523). With his unique artworks, the painter used the gruesome appearance of the supernatural to give casual viewers a nice "safe" scare. His depictions also made the well-educated think about the erotic charisma of women, love and its possible consequences, and female beauty and its mysteries. Using his art, Grien not only ironically comments on medieval attitudes towards witches, but also on the artistic theories of his master, Albrecht Durer."--Amazon.com